EXAMINING EFL CLASSROOM INTERACTION BASED ON SINCLAIR AND COULTHARD MODEL - Nurul Wulanda; Anni Holila Pulungan; Isli Iriani Indiah Pane (Universitas Negeri Medan, 2017)
The aim of this study were (a) to identify classroom discourse patternings of EFL classroom interaction based on Sinclair and Coulthard Model, and (b) to describe how EFL classroom interaction affects the students’ learning process based on Sinclair and Coulthard Model. The subject of this study were an English Teacher, and 40 students of XI MIA 1, SMA Swasta Nurul Iman. The instrument for collecting data were observation and recording. The result of this research were the following, (a) it was found that in the classroom discourse, there were seven patterns initiated by the teacher and four patterns initiated by the student as the IRF (Initiation-Response-Feedback) was used more often by the teacher, (b) the interaction affects the teaching learning process in a way how the lesson passed on to the student affects the goal of learning English itself to be able to use English both inside and outside the classroom. It can be concluded that the students were not getting used to interact with English, and the goal of communicative skill in English was not achieved. Thus, the teachers should reorganize the activities which can foster more interaction by using English in the classroom. Keywords: Classroom interaction, classroom discourse, Sinclair and Coulthard, IRF Pattern.